Use of pheromone trap and vermicompost for the success of vegetable growers of Bundelkhand, Uttar Pradesh - Manjunatha, N; Mahesha, H S; Choudhary, Bishwa Bhaskar; Sharma, Purushottam; Kumar, Sunil; Chaudhary, Mukesh; Singh, S K; Dwivedi, R P; Dubey, Shantanu Kumar; Chandra, Avinash; Saxena, A K; Sachendra; et al. (Indian Farming, 2022)
It is clearly indicated that pheromone traps along with bio-pesticides and vermicompost offer considerable level of protection against targeted pest and reducesthe production cost and increases the net returns to the farmers. Besides, it reduces the pesticide dumping in the vegetable production. This eco-friendly method has many advantages over chemical pesticides including low cost, safe to non-target organisms and environment, less labour intensive, easy to operate and residue free products.